Gender-preferential interjections in Japanese manga Akuyakureijouttekoto - Pika Yestia Ginanjar (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2026)
Japanese interjections (kandoushi) play an important role in expressing emotions, responses, and social relationships. While previous studies have examined kandoushi from grammatical, pragmatic, and semantic perspectives, little attention has been given to how gender-preferential language is represented through interjections in fictional discourse. This study investigates the use of Japanese interjections by female (ojousama) and male (oujisama) characters in the shoujo manga Akuyakureijoutte koto. Employing a descriptive qualitative method supported by simple quantitative analysis, the study analyzes 346 interjection utterances collected from Volumes 1–3 using the yakuwarigo framework. The findings reveal that all three categories of Japanese interjections—kandoushi (emotive), outoushi (response), and yobikakeshi (vocative)—are used by both genders; however, significant differences emerge in their frequency, lexical preferences, and contextual meanings. Female characters employ a wider variety of emotive interjections and express emotional nuances such as enthusiasm, satisfaction, and affectionate playfulness more frequently, whereas male characters predominantly use interjections associated with responses, calls, and situational awareness. These findings demonstrate that interjections function not only as emotional expressions but also as linguistic markers that construct gendered character identities within the yakuwarigo system in contemporary Japanese manga.